Telling stories out of court : narratives about women and workplace discrimination - O'Brien, Ruth, 1960- (Cornell University Press, 2008)
""Few of the countless real-life stories of workplace discrimination suffered by men and women every day are ever told publicly. This book boldly and eloquently rights that wrong, going where no plaintiff testimony could ever dare because these stories...